Etika Khitbah Dalam Pandangan Hadis Nabi Saw. (Studi Pemahaman Masyarakat Kelurahanin Binjai Serbangan Kecamatan Air Joman) - Pranata, Mhd Ridho (SHAHIH (Jurnal Ilmu Kewahyuan), 2024)
This research aims to examine in depth the ethics of sermons from the perspective of the hadith of the Prophet Muhammad. preaching ethics. By understanding the ethics of proposing marriage taught in the hadith, it is hoped that we can provide comprehensive guidance for Muslims in carrying out the proposing procession in accordance with Islamic values. The results of the research were by applying the hadiths obtained from the Maktabah Syamilah application by selecting hadiths of shohih quality. And can be practiced in life.